Compulsive methamphetamine self-administration in the presence of adverse consequences is associated with increased hippocampal mRNA expression of cellular adhesion molecules - Munoz, Ceiveon; Jayanthi, Subramaniam; Ladenheim, Bruce; Cadet, Jean Lud (Frontiers in Molecular Neuroscience, 2023)
Methamphetamine (METH) is a popular but harmful psychostimulant. METH use disorder (MUD) is characterized by compulsive and continued use despite adverse life consequences. METH users experience impairments in learning and memory functions that are thought to be secondary to METH-induced abnormalities in the hippocampus. Recent studies have reported that about fifty percent of METH users develop MUD, suggesting that there may be differential molecular effects of METH between the brains of individuals who met criteria for addiction and those who did not after being exposed to the drug. The present study aimed at identifying potential transcriptional differences between compulsive and non-compulsive METH self-administering male rats by measuring global gene expression changes in the hippocampus using RNA sequencing. Herein, we used a model of METH self-administration (SA) accompanied by contingent foot-shock punishment. This approach led to the separation of animals into shock-resistant rats (compulsive) that continued to take METH and shock-sensitive rats (non-compulsive) that suppressed their METH intake in the presence of punished METH taking. Rats were euthanized 2 hours after the last METH SA plus foot-shock session. Their hippocampi were immediately removed, frozen, and used later for RNA sequencing and qRT-PCR analyses. RNA sequencing analyses revealed differential expression of mRNAs encoding cell adhesion molecules (CAMs) between the two rat phenotypes. qRT-PCR analyses showed significant higher levels of Cdh1, Glycam1, and Mpzl2 mRNAs in the compulsive rats in comparison to non-compulsive rats. The present results implicate altered CAM expression in the hippocampus in the behavioral manifestations of continuous compulsive METH taking in the presence of adverse consequences. Our results raise the novel possibility that altered CAM expression might play a role in compulsive METH taking and the cognitive impairments observed in MUD patients.